SISTEM PRESENSI ONLINE GURU DAN SISWA MENGGUNAKAN QR CODE DI SMK AL HASYIMY BANTAL - Ahmad Muzakki; Raka Dwi Fachrul Hamzah; Risky Kenedy Ramadhani; Musthofa Ali Rofi'i; Abdus Samad (Jurnal Riset Teknik Komputer, 2026)
The development of information technology has greatly influenced various aspects of education, including the attendance administration system for teachers and students. Manual attendance processes still have several weaknesses, such as data recording errors, attendance manipulation risks, and time-consuming recap processes. This research aims to develop an online attendance system for teachers and students using QR Code at SMK Al Hasyimy Bantal as a solution to replace the existing manual attendance system and improve the effectiveness and efficiency of attendance management. The research methods used include observation, interviews, and literature studies, while the system development method employs the Waterfall model. The system was developed as a website-based application using the PHP programming language and MySQL database. The results show that the QR Code-based attendance system successfully automates the attendance recording process in real-time, facilitating the monitoring of teacher and student attendance data. In addition, the system accelerates the attendance process, minimizes data recording errors, and simplifies attendance report generation. With this system, the attendance administration process at SMK Al Hasyimy Bantal becomes more structured, faster, and integrated.